Accounting Balancing Game as a Supplementary Teaching tool to Improve Diploma in Accountancy UiTM Students' Performance on Accounting Principles - Narawi, Susana (UITM Sarawak,Kampus Samarahan, 2011)
Financial accounting paper's performance among accounting students is important factor as it is a core subject. However based on Diploma of Accountancy previous semester's result in Universiti Teknologi MARA Sarawak, the performance in financial accounting papers has always been unsatisfactory. Among the comments highlighted in the chief examiner's report on the unsatisfactory performance of financial accounting paper was due to some students' poor understanding of accounting principles. Accounting principles are taught in semester 1 and 2 and the students are required to have a strong understanding of these principles. Thus, if the students are not able to master the accounting principles at the elementary stage, they will face more difficulties in attempting financial accounting paper at higher levels. The purpose of this study is to identify the impact of the Accounting Balancing Game on the student's performance on accounting principles and therefore it will be part of the instruments to be utilized for the experimental group under this study. Accounting Balancing Game has been created with the intention to integrate fun within learning process. In addition it requires its participants to acknowledge the significance of time management in solving accounting principles problems. The Accounting Balancing Game inventors are planning to submit the game as an innovation for Invention, Innovation and Design 2009 Competition. Hence, it is essential that this innovation be tested as the findings and results from this research will be further improved. In addition, any favourable results obtained from the research will be a value-added element as the Accounting Balancing Game can be commercialized as a supplementary tool to enhance student's understanding of the financial accounting subject both at secondary school and university level.